2016
DOI: 10.1021/acs.macromol.6b00469
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Conductive PEBA Copolymer at the Continuous Interface in Ternary Polymer Systems: Morphology and Resistivity

Abstract: Two ternary blend systems of low-density polyethylene/poly­(ether-block-amide)/polyethylene terephthalate (LDPE/PEBA/PET) and LDPE/PEBA/polyvinylidene fluoride (PVDF) are prepared by melt blending to thermodynamically assemble the ionically conductive PEBA copolymer at the continuous interface. The LDPE/PEBA/PET blend demonstrates weak partial wetting and a novel morphology transition to complete wetting was observed as the PEBA composition increases from 3% to about 10%. The phenomena can be explained by a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(74 citation statements)
references
References 61 publications
4
69
1
Order By: Relevance
“…Looking to the experimentally determined values of polymer/polymer interfacial tension and the calculated spreading coefficient value (λ PLA/PBS/PCL = −0.58 mN/m 43 ), which is negative but close to zero, one can predict a weak partial wetting regime for this system. On the other hand, Wang et al 33 reported that the annealing of concentrated partially wet droplets can result in a partial to complete wetting transformation by forming thin completely wet layers, which in time tend to de‐wet and return to the initial thermodynamically stable partial wetting morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking to the experimentally determined values of polymer/polymer interfacial tension and the calculated spreading coefficient value (λ PLA/PBS/PCL = −0.58 mN/m 43 ), which is negative but close to zero, one can predict a weak partial wetting regime for this system. On the other hand, Wang et al 33 reported that the annealing of concentrated partially wet droplets can result in a partial to complete wetting transformation by forming thin completely wet layers, which in time tend to de‐wet and return to the initial thermodynamically stable partial wetting morphology.…”
Section: Resultsmentioning
confidence: 99%
“…19 Recently, multicomponent immiscible blends (blends with more than two components) have attracted considerable attention due to their mechanical performance enhancement and other functional application potential. [29][30][31][32][33] Two main types of morphology can be obtained in multiphase polymer blends with three components (e.g., immiscible ternary blends with two major components and one minor phase), which are complete wetting and partial wetting. In the latter, the minor component is present as droplets self-assembled at the interface of the other two major components.…”
mentioning
confidence: 99%
“…When all three spreading coefficients are negative, the system tends to minimize interfacial energy by forming three-phase contact, defined as "partial wetting," Figure 1(d). 21,22,23 The literature reports on PE/PS and PS/PLA interfacial tensions are presented in Table 2. According to Carriere et al, 24 the temperature dependence of PE/PS interfacial tension goes as Γ = 7.6-0.015 T mN/m, where T is temperature in C. And Wu 25 reported a similar one, Γ = 8.3-0.020(T-20) mN/m.…”
Section: Introductionmentioning
confidence: 99%
“…The oligomeric prepolymers with low glass transition temperature (T g ) were frequently used as the soft segments in the polyamide‐based block copolymer in the previous study . P.A.M. Lips prepared a series of poly(ester amide)s with different PA6 hard segments and poly(butylenes adipate) soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The oligomeric prepolymers with low glass transition temperature (T g ) were frequently used as the soft segments in the polyamide-based block copolymer in the previous study. 12,16,17 P.A.M. Lips 18 prepared a series of poly(ester amide)s with different PA6 hard segments and poly(butylenes adipate) soft segments. The obtained poly(ester amide)s exhibited obvious crystalline hard segments and with the increasing of PA6 hard segments content from 10 to 85 mol% the high melt transition increased from 83°C to 140°C.…”
Section: Introductionmentioning
confidence: 99%